Tahiti Nui Change and Survival in French Polynesia, 1767-1945 - Newbury, Colin W. (University of Hawai'i Press, 2018)
Tahiti Nui is an account of the survival of a Polynesian society in the face of successive settlements of missionaries, traders, and administrators. Beginning with the first explorers and Captain Cook's scientific observations at Point Venus, Dr. Newbury has separated the various strands interwoven in the fabric of Tahitian society, tracing their development and showing how they interacted at successive stages. Missionaries and foreign traders, administrators and Polynesians, planters and immigrant Chinese have all contributed to the distinctive flavor of French Polynesia, with Tahiti and Tahitians becoming increasingly dominant, not just as the focus of the French administration in Pape'ete, but in the social networks and trading patterns that have evolved.